Cryptocurrency and anti-money laundering law: the need for an integrated approach - Zul Kepli, Mohd Yazid; Zulhuda, Sonny (2018)
This article attempts to clarify and describe the legal and regulatory framework for cryptocurrency and the threats that it posed from the anti-money laundering perspective. Currently, very few countries have legislations that regulate cryptocurrency. Nonetheless, the crazy surge in prices (to more than 20-fold) has sent both legitimate investors and criminals flocking to cryptocurrencies. The article analyzes and compares the official reports from various governments, writings by government officials, experts and scholars in journals and newspapers, interviews and draws conclusions on the legal framework of cryptocurrency, and money laundering challenges. This article founds that the decision of the United States regulators in allowing bitcoin futures to trade on major exchanges to be one of the reasons behind the sudden surge. This article also founds that the South Korean regulators approach in banning its financial institutions from dealing with virtual currency is a positive one. The article stresses that it is not adequate for regulators to warn the public to act with extreme caution and to increase their understanding on the risks they take on if they choose to invest in cryptocurrencies. Instead, it is indispensible to have comprehensive international and national laws and regulations for the control and management of cryptocurrencies. In addition, the anti-money laundering legal framework must be improved to cater to the new threats posed by cryptocurrency.